The Circular Economy Approach to Improving CNP Ratio in Inland Fishery Wastewater for Increasing Algal Biomass Production (2022)
In this work, the capacity of wastewater from an inland fishery system in Colombia (Norte de Santander) was tested as culture medium for Chlorella sp. and Scenedesmus sp. Due to insufficient N and P concentrations for successful algae growth, the effect of wastewater replenishment with NO3 , PO4 , and Na2CO3 or NaHCO3 as a carbon source was analyzed using a three-factor nonfactorial response surface design. The results showed that the addition of NaNO3 (0.125 g/L), K2HPO4 (0.075 g/L), KH2PO4 (0.75 g/L), and NaHCO3 (0.5 and 2 g/L for Chlorella sp. and Scenedesmus sp. respectively) significantly increased the biomass of Chlorella sp. (0.87 g/L) and Scenedesmus sp. (0.83 g/L). Although these results show that the addition of other nutrients is not necessary (Na, Mg, SO4 , Ca, etc.), it is still essential to determine the quality of the biomass produced in terms of its application as a feed supplement for fish production.